Financial Reporting Quality and Investment Efficiency: Evidence from Indonesian Stock Market - Hanif Putra Ardianto; Iman Harymawan; Yuanita Intan Paramitasari; Mohammad Nasih (Economics and Finance in Indonesia, 2020)
This study aims to analyze the impact of financial reporting quality on the investment efficiency of a company. The study uses 994 observations from companies listed on the Indonesia Stock Exchange (IDX) in three periods from 2013 to 2015. The findings suggest that higher financial reporting quality has a positive and significant relationship with investment efficiency. Furthermore, the tests were conducted on groups of companies experiencing underinvestment and overinvestment. It was found that higher financial reporting quality had a negative and significant relationship with companies experiencing overinvestment. The findings provide implications for investors in assessing investment management carried out by company.